Peningkatan keselamatan kerja pada proyek pembangunan gedung sekolah dasar (SD) Islam Karakteristik di Kabupaten Aceh Besar - Aulia Rahman; Alvisyahri Alvisyahri; Bambang Tripoli; Rahmat Djamaluddin (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
Building construction projects are among the construction activities with the highest risk of occupational accidents. This community service program examined the extent to which Occupational Safety and Health (OSH) practices were implemented in the construction of the Islamic Character Elementary School building in Aceh Besar Regency. The program was conducted through three stages: an initial approach and observation of work habits (baseline assessment), practical demonstrations and on-site assistance (action and coaching), and behavioral monitoring and impact evaluation. These activities involved construction workers, forepersons, project supervisors, and representatives of the school. The program aimed to obtain a systematic and factual understanding of OSH implementation at the project site. The findings showed that OSH practices had been introduced and partially implemented; however, their application remained suboptimal. Several workers still demonstrated limited compliance with safety procedures and the use of personal protective equipment. These findings indicate the need for continuous supervision, regular safety training, and stronger commitment from all parties involved in the construction project.